Wnt/β-catenin-activated nonpilomatrical carcinoma of the skin: a case series - Kervarrec, Thibault; Cheok Lei, Kuan; Sohier, Pierre; Macagno, Nicolas; Jullie, Marie-Laure; Frouin, Eric; Goto, Keisuke; Taniguchi, Kohei; Hamard, Aymeric; Taillandier, Antoine; Tallet, Anne; Bonenfant, Christine; et al. (Modern pathology, 2024)
Among skin epithelial tumors, recurrent mutations in the APC/CTNNB1 genes resulting in activation of the Wnt/β-catenin pathway have been reported predominantly in neoplasms with matrical differentiation. In the present study, we describe the morphologic, immunohistochemical, and genetic features of 16 primary cutaneous carcinomas harboring mutations activating the Wnt/β-catenin pathway without evidence of matrical differentiation, as well as 4 combined tumors in which a similar Wnt/β-catenin-activated carcinoma component was associated with Merkel cell carcinoma (MCC) or pilomatrical carcinoma. Among the pure tumor cases, 6 of 16 patients were women with a median age of 80 years (range, 58-98 years). Tumors were located on the head and neck (n = 7, 44%), upper limb (n = 4, 25%), trunk (n = 3, 18%), and leg (n = 2, 13%). Metastatic spread was observed in 4 cases resulting in death from disease in 1 patient. Microscopically, all cases were poorly differentiated neoplasms infiltrating the dermis and/or subcutaneous tissue. In 13 cases, solid “squamoid” areas were associated with a basophilic component characterized by rosette/pseudoglandular formation resulting in a biphasic appearance. Three specimens consisted only of poorly differentiated carcinoma lacking rosette formation. Immunohistochemical studies showed frequent expression of EMA (100%), BerEP4 (100%), cytokeratin 7 (94%), chromogranin A (44%), synaptophysin (82%), and cytokeratin 20 (69%). Complete loss of Rb expression was observed in all but 1 case. Nuclear β-catenin and CDX2 expressions were detected in all cases. Recurrent pathogenic somatic mutations were observed in APC (60%), CTNNB1 (40%), and RB1 (n = 47%). Global methylation analysis confirmed that cases with rosette formation constituted a homogeneous tumor group distinct from established skin tumor entities (pilomatrical carcinoma, MCC, and squamous cell carcinoma), although the 3 other cases lacking such morphologic features did not. In addition, we identified 4 combined neoplasms in which there was a component showing a similar poorly differentiated rosette-forming carcinoma demonstrating Rb loss and β-catenin activation associated with either MCC (n = 3) or pilomatrical carcinoma (n = 1). In conclusion, we describe a distinctive neoplasm, for which we propose the term “Wnt/β-catenin-activated rosette-forming carcinoma,” morphologically characterized by the association of rosette formation, squamous and/or neuroendocrine differentiation, diffuse CDX2 expression, Rb loss, and mutations in CTNNB1/APC genes.
Gesehen am 23.05.2025